2019
DOI: 10.18203/2349-3933.ijam20191161
|View full text |Cite
|
Sign up to set email alerts
|

Association between glycemic control and serum fibrinogen levels in type 2 diabetes mellitus patients

Abstract: Background: Poor glycemic control has been reported to be associated with increased vascular complications in diabetes mellitus (DM) patients.  High fibrinogen level has been described as an independent risk factor for cardiovascular diseases. High fibrinogen has been suggested to be involved in the excess rate of cardiovascular diseases in patients with type 2 DM. The present study was undertaken to find correlation between glycemic control and plasma fibrinogen level in patients with type 2 DM.Methods: Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Topiwala et al . [ 25 ] found that 87 (28.0%), 89 (28.7%) and 134 (43.2%) patients had a BMI <23.0, 23.0 to <25.0 and ≥25.0 kg/m 2 , respectively, in diabetic patients. Kumbhalkar and Daware[ 26 ] found that the maximum number of patients (60%) of both groups had grade II obesity (BMI >30 to 40).…”
Section: Discussionmentioning
confidence: 99%
“…Topiwala et al . [ 25 ] found that 87 (28.0%), 89 (28.7%) and 134 (43.2%) patients had a BMI <23.0, 23.0 to <25.0 and ≥25.0 kg/m 2 , respectively, in diabetic patients. Kumbhalkar and Daware[ 26 ] found that the maximum number of patients (60%) of both groups had grade II obesity (BMI >30 to 40).…”
Section: Discussionmentioning
confidence: 99%